Adeno-associated virus-based gene therapy for hemophilia–addressing the gaps - Wolfgang Miesbach; Paul Batty; Pratima Chowdary; Sylvia Fong; Radoslaw Kaczmarek; Frank W.G. Leebeek; Brian Long; Johnny Mahlangu; Mike Makris; Glenn F. Pierce; Steven W. Pipe; Alok Srivastava; et al. (Research and Practice in Thrombosis and Haemostasis)
Adeno-associated virus-based gene therapy for hemophilia has emerged as a revolutionary treatment option, offering potential correction of clotting factor deficiency through a single intravenous infusion of functional genes directed to hepatocytes. With 3 gene therapies recently approved, this approach shows promise in transforming the lives of individuals with hemophilia. However, the complexity of gene therapy and the lack of standardization of methods in different components of this therapy can lead to unique challenges for clinical implementation. This manuscript follows literature reviews and structured discussions by the International Society on Thrombosis and Haemostasis Scientific and Standardization Committee Working Group on Gene Therapy that identified specific areas requiring standardization of methods, including viral vector production, liver function assessment, quantification of factor (F)VIII and FIX expression levels, assessment of antiadeno-associated viral antibodies, and genomic integration detection methods. Standardization strategies aim to achieve consistent vector quality, effective patient selection, and uniform assessment methods by implementing advanced laboratory techniques and standardized protocols. Standardizing these parameters is essential for improving the understanding of short-term and long-term safety and efficacy of gene therapy in hemophilia. This effort aims to enhance the predictability of individual responses, address variability in outcomes, and ultimately provide more effective, safer, and personalized treatment options for individuals with hemophilia.